Researching How AI Works Marketing Influence Trust Consumers In Two Culture Different - Elsa Islammia Pasha (Politeknik Siber Cerdika Internasional, 2025)
Development rapidly intelligence artificial intelligence (AI) in digital marketing strategy has bring up challenge new in understand dynamics trust consumer cross culture . In an increasingly global context connected , important For evaluate How perception consumer to use of AI in marketing different between culture , especially related with aspect privacy , personalization , and transparency . Article This aim For research influence use of AI in marketing to trust consumers in two culture different , namely culture individualistic ( United States ) and culture collectivism (Indonesia). Research This use approach quantitative with method survey , involving 400 respondents who were divided equally between the two countries . The instruments used is questionnaire closed with Likert scale for measure perception trust , AI transparency , and value culture consumers . Data analysis was carried out using Structural Equation Modeling (SEM) to test connection between variables . The results show that AI in marketing own influence positive to trust consumers , however mediated in a way significant by value culture . Consumers in culture individualistic more value personalization and data control , while consumers in culture collectivistic more influenced by opinion social and trust institutional findings​ This give outlook important for global companies for adjust marketing strategy AI -based according to with context target culture .​